COUNTERING CYBER ESPIONAGE CRIMES WITH CRIMINAL LAW MEANS - Muh. Sanjaya Sakti; Khalid Usman; Muhammad Wahyudin Naskun (Program Studi Ilmu Hukum Universtitas Muhammadiyah Gorontalo, 2026)
Cyber espionage crime is a form of cybercrime that has a strategic impact on national security, the economy, and individual privacy. This article analyzes the phenomenon of cyber espionage through a routine activity theory approach, focusing on three main elements: motivated perpetrators, decent targets, and the absence of effective guards and efforts to counter cyber espionage crimes within the rule of law in Indonesia. This research is normative juridical, with a conceptual, legislative approach, and uses secondary data that includes primary legal materials. In this study, the perpetrators are generally state actors or state-sponsored groups with high technical capabilities, while the target is digitally vulnerable strategic data. Weak legal protection and inadequate cybersecurity infrastructure result in ineffective prevention mechanisms. The results of this study show that, first, Indonesia does not yet have criminal law norms that explicitly regulate the crime of cyber espionage, thereby creating a legal vacuum and uncertainty for law enforcement. Second, the routine activity theory approach is very relevant to understanding the dynamics of cyber espionage crimes and urges the need to reform national criminal laws, strengthen digital security systems, and improve cyber literacy to strengthen the